Na+,K+-ATPase with Disrupted Na+ Binding Sites I and III Binds Na+ with Increased Affinity at Site II and Undergoes Na+-Activated Phosphorylation with ATP - Hang N. Nielsen; Rikke Holm; Ryan Sweazey; Jens Peter Andersen; Pablo Artigas; Bente Vilsen (Biomolecules, 2024)
Na+,K+-ATPase actively extrudes three cytoplasmic Na+ ions in exchange for two extracellular K+ ions for each ATP hydrolyzed. The atomic structure with bound Na+ identifies three Na+ sites, named I, II, and III. It has been proposed that site III is the first to be occupied and site II last, when Na+ binds from the cytoplasmic side. It is usually assumed that the occupation of all three Na+ sites is obligatory for the activation of phosphoryl transfer from ATP. To obtain more insight into the individual roles of the ion-binding sites, we have analyzed a series of seven mutants with substitution of the critical ion-binding residue Ser777, which is a shared ligand between Na+ sites I and III. Surprisingly, mutants with large and bulky substituents expected to prevent or profoundly disturb Na+ access to sites I and III retain the ability to form a phosphoenzyme from ATP, even with increased apparent Na+ affinity. This indicates that Na+ binding solely at site II is sufficient to promote phosphorylation. These mutations appear to lock the membrane sector into an E1-like configuration, allowing Na+ but not K+ to bind at site II, while the cytoplasmic sector undergoes conformational changes uncoupled from the membrane sector.